Empowering Women Leaders : Analyzing Organizational Support Mechanisms and Their Effectiveness in the Czech Republic - Najmanová, Tereza; Pauknerová, Daniela, 1970-; Honsová, Pavlína; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This Master’s Thesis explores the underrepresentation of women in leadership roles in the Czech Republic. It identifies key structural, cultural, and psychological barriers - such as gender bias, limited mentorship, and challenges around maternity leave - through qualitative interviews with 14 women in managerial positions. The findings reveal that support mechanisms like mentoring, leadership development training, and flexible work arrangements play a crucial role in women’s career advancement. The thesis offers practical recommendations for Czech organizations to improve gender inclusivity and argues that fostering female leadership enhances long-term organizational success. These insights provide a foundation for both future research and policy implementation.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses